2019
DOI: 10.1128/iai.00205-19
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus T Antigens Have a Highly Conserved Structure Concealed under a Heterogeneous Surface That Has Implications for Vaccine Design

Abstract: Group A Streptococcus (GAS) (Streptococcus pyogenes) is an important human pathogen associated with significant global morbidity and mortality for which there is no safe and efficacious vaccine. The T antigen, a protein that polymerizes to form the backbone of the GAS pilus structure, is a potential vaccine candidate. Previous surveys of the tee gene, which encodes the T antigen, have identified 21 different tee types and subtypes such that any T antigen-based vaccine must be multivalent and carefully designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Previous bioinformatic analysis of two-domain T-antigens revealed a highly conserved core decorated by surface variation along the full length of the protein, with no apparent dominant region 31 . We therefore designed a multivalent vaccine that included whole T-antigen domains to maximise both the inclusion of protective epitopes and protein yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous bioinformatic analysis of two-domain T-antigens revealed a highly conserved core decorated by surface variation along the full length of the protein, with no apparent dominant region 31 . We therefore designed a multivalent vaccine that included whole T-antigen domains to maximise both the inclusion of protective epitopes and protein yield.…”
Section: Resultsmentioning
confidence: 99%
“…TeeVax1 was constructed as a fusion of alternating N- and C-terminal domains from six different two-domain T-antigens to resemble a hybrid pilus fibre. Primers were designed based on the predicted boundaries for each domain generated from these models 31 . The BamHI restriction site was engineered at the 5′ end, and BglII and EcoRI restriction sites were engineered at the 3′ end of each domain, introduced by the PCR primers (Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike a multivalent M protein vaccine, there are fewer T type variations. However, comparative structural analyses of three two-domain T antigens (FctA), including T3, T13, and T18, revealed that the overall core structure is conserved and variations are distributed through the entire region ( Young et al, 2019 ). Ideally, a candidate vaccine antigen would comprise a multivalent linkage of whole T antigens or domains.…”
Section: Discussionmentioning
confidence: 99%